2018
DOI: 10.1080/00016489.2018.1438662
|View full text |Cite
|
Sign up to set email alerts
|

Definitive re-irradiation using intensity-modulated radiation therapy in cancers of the head and neck, focusing on rare tumors

Abstract: Re-irradiation of rare head and neck tumors using IMRT for loco-regional recurrence may be an acceptable treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The two-year overall survival rates for recurrent/locally advanced SCC and non-SCC were 58% and 100%, respectively. There are a few reirradiation series for external auditory canal malignancies [13,22]. Our data also implied poorer outcome of SCC than non-SCC.…”
Section: Auditory Organ Cancermentioning
confidence: 55%
“…The two-year overall survival rates for recurrent/locally advanced SCC and non-SCC were 58% and 100%, respectively. There are a few reirradiation series for external auditory canal malignancies [13,22]. Our data also implied poorer outcome of SCC than non-SCC.…”
Section: Auditory Organ Cancermentioning
confidence: 55%
“…However, advanced radiotherapy, IMRT, image-guided radiotherapy, and stereotactic radiotherapy (SBRT) allow the application of high doses to complex volumes while sparing the surrounding organs at risk, with low toxicity [ 13 , 14 ]. Several authors have reported their reirradiation experiences with IMRT or SBRT in <10 patients [ 14 , 20 , 21 ]. Iwata et al [ 9 ] reported the treatment results of 51 patients with locally recurrent nasal and paranasal carcinoma using CyberKnife with a prescribed median dose of 35 Gy (range, 20–41.5 Gy) in 3–5 fractions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, IMRT has been widely used in the treatment of various head and neck tumours, including NPC and other rare cancers. 19 , 20 In addition, a clinical study reported that IMRT not only significantly improved treatment outcomes but also reduced the incidence of some side effects. 21 Intensity-modulated radiation allows the clinician to adjust the intensity of each radiation according to the actual situation, so each beam field can have one or more high-intensity radiation areas and any number of low-intensity areas within the same field, thus allowing greater control over the dose distribution with the target.…”
Section: Methodsmentioning
confidence: 99%